VD_FINDINFO Jug / 2025 / 92 vom 29. Juli 2024 - VD Tribunal cantonal (2024)
ANNONCE D'APPEL, DÉLAI, DÉCISION D'IRRECEVABILITÉ | 399 al. 3 CPP (CH), 403 al. 1 let. a CPP (CH), 85 al. 4 let. a CPP (CH), 91 CPP (CH)